2022
DOI: 10.1007/s10661-022-10803-4
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining urban forest monitoring based on a large-scale tree survey: a case study of highway vegetation in Hong Kong

Abstract: Urban tree monitoring is essential to successful urban forestry. Transport land use accommodates huge tree stock which require substantial monitoring efforts. In Hong Kong, more research is needed to take into considerations how monitoring works can be modi ed in response to variations in tree stand characteristics. This case study aimed to illustrate the usefulness of a large-scale tree survey in mainstreaming future tree monitoring and management in transport land use. 7,209 trees were found in a large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…This study provides evidence, combined with other precautions, that specific analyses performed on open data could help in the optimization process of the management of urban trees. Below are some inputs and suggestions on how to optimize the urban tree management: maximize the positive effects of vegetation on the urban environment through integrated and innovative management capable of combining environmental needs with economic ones [87][88][89]; promote knowledge and monitoring of the natural heritage of urban greenery through innovative mapping and representation tools [90,91]; make the management interventions of the urban greenery system systematic and homogeneous by preparing appropriate plans and programs [92,93]; carry out maintenance interventions according to the most up-to-date criteria and in compliance with scientifically based cultivation techniques aimed at reducing external inputs [94][95][96]; guarantee transparency in every action and make citizens an active part in the knowledge and care of greenery through communication, information, teaching, and active discussion actions [97,98]. Among these, the implementation of a tool using open data and providing quantitative evaluation for the assessment of trees' failure risk could provide an interesting contribution to the scientific discussion on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides evidence, combined with other precautions, that specific analyses performed on open data could help in the optimization process of the management of urban trees. Below are some inputs and suggestions on how to optimize the urban tree management: maximize the positive effects of vegetation on the urban environment through integrated and innovative management capable of combining environmental needs with economic ones [87][88][89]; promote knowledge and monitoring of the natural heritage of urban greenery through innovative mapping and representation tools [90,91]; make the management interventions of the urban greenery system systematic and homogeneous by preparing appropriate plans and programs [92,93]; carry out maintenance interventions according to the most up-to-date criteria and in compliance with scientifically based cultivation techniques aimed at reducing external inputs [94][95][96]; guarantee transparency in every action and make citizens an active part in the knowledge and care of greenery through communication, information, teaching, and active discussion actions [97,98]. Among these, the implementation of a tool using open data and providing quantitative evaluation for the assessment of trees' failure risk could provide an interesting contribution to the scientific discussion on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gülçin (2020) found that floristic species richness in urban forests affects the occurrence of urban birds and tree canopies of the vegetation have cooling effects on the microclimate conditions. Therefore, assessment and monitoring of vegetation, especially trees, are essential when implementing green space in urban areas (Lee et al 2023). Some considerations when choosing vegetation type and plant species in urban forests include high tolerance to harsh environmental conditions in urban area, resistant to diseases, not infectious, and long-lived.…”
Section: Introductionmentioning
confidence: 99%